A method for producing wood-steel

CN122876494APending Publication Date: 2026-10-09GUANGDONG TECHNION ISRAEL INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611056451.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-16
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

②真空干燥法,在减压条件下促进水分蒸发,但设备成本较高

Benefits of technology

1)与水的相容性:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122876494A_ABST
    Figure CN122876494A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of materials, and particularly discloses a preparation method of wood steel. The application adopts a mixed solution and anthraquinone to catalyze the decomposition of lignin and hemicellulose in wood, and then adopts a high-temperature ultrasonic cooking mode to decompose the lignin and hemicellulose in the wood, so that softened wood (water content is more than 50%) is obtained; then the softened wood after cleaning is immersed in an organic solvent to replace the water in the wood, and the wood is subjected to hot-press drying, so that wood steel is obtained. The preparation method provided by the application can realize the rapid drying of hot-pressed wood at a low drying temperature, avoids the deepening of the color of the wood in the drying process, reduces the internal stress and structural defects caused by drying, and further optimizes the chemical composition (lignin / hemicellulose) of the wood in the drying process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of materials technology, and in particular to a method for preparing wood-steel composites. Background Technology

[0002] Currently, the preparation of densified wood, or "wood-steel," typically includes the following steps: 1) Wood pretreatment: The wood planks are first boiled in a high-temperature alkaline solution to remove most of the lignin and hemicellulose, and to soften the planks; 2) Wood washing: The wood planks are washed repeatedly with large amounts of hot water to remove residual chemical reagents and to a pH neutral state; 3) Hot-press densification: The wood planks are placed in a mold, and pressure is applied from above to squeeze out most of the moisture. Simultaneously, the voids formed after the removal of lignin and hemicellulose are compacted, reducing the thickness of the wood and increasing its density several times over; 4) Drying: In the drying stage, the mainstream technical routes include: ① High-temperature drying: High pressure is applied to the wood planks while heating, causing the residual moisture inside the wood to evaporate through the fiber channels. ② Vacuum drying: Moisture evaporation is promoted under reduced pressure, but the equipment cost is high. ③ Natural drying or staged drying: This method is time-consuming, inefficient, and the wood's interior is difficult to dry, resulting in large differences in moisture distribution, making it difficult to industrialize.

[0003] The above-mentioned preparation methods have the following disadvantages: 1) Long drying cycle: Traditional methods usually require tens of hours to several days, which seriously restricts production efficiency. 2) Easily leads to darkening of wood color: Incomplete removal of lignin, or thermal degradation of lignin under high temperature conditions, results in significant darkening and carbonization of the wood, and uneven color of the boards. 3) Easily generates internal stress and defects: cracking, warping, and internal stress concentration. 4) High energy consumption: Long-term high-temperature drying consumes a lot of energy, which is not conducive to large-scale low-cost production. Summary of the Invention

[0004] The purpose of this application is to overcome the shortcomings of the prior art and provide a method for preparing wood-steel.

[0005] To achieve the above objectives, the technical solution adopted in this application is as follows: This application provides a method for preparing wood-steel composites, comprising the following steps: 1) Soak natural wood in a mixed solution of NaOH and Na2SO3, add anthraquinone as a catalyst, and then ultrasonically cook it at a temperature of 80~120℃ to obtain softened wood; 2) Ultrasonic cleaning of the softened wood from step 1), then immersing the cleaned wood in an organic solvent, ultrasonically displacing the moisture from the wood to obtain the treated wood. 3) The wood treated in step 2) is hot-pressed and dried to obtain wood-steel; The organic solvent has a boiling point below 100℃ and is miscible with water.

[0006] This application provides a method for preparing wood-steel composite suitable for industrialization and with low energy consumption. It can achieve rapid drying of hot-pressed wood under low-temperature conditions, avoid the darkening of wood color during the drying process, reduce internal stress and structural defects caused by drying, and further optimize the chemical composition of wood (lignin / hemicellulose) during the drying process.

[0007] This application employs a mixed solution and anthraquinone to catalyze the decomposition of lignin and hemicellulose in wood. High-temperature ultrasonic cooking further decomposes the lignin and hemicellulose, yielding softened wood (moisture content above 50%). The softened wood is then immersed in an organic solvent to displace the moisture, followed by hot-press drying to obtain wood-steel. The use of a water-miscible solvent ensures that it can diffuse into the wood cell cavities and cell walls, effectively replacing free water and some bound water. Simultaneously, the solvent's boiling point is below 100℃, allowing for rapid evaporation at lower temperatures during subsequent hot-pressing, improving drying efficiency and reducing energy consumption. Furthermore, the organic solvent with these characteristics can partially dissolve lignin or hemicellulose, further reducing the content of non-cellulose components in the wood during the replacement process, and can also enter the microporous structure through capillary action, improving replacement efficiency.

[0008] In a preferred embodiment of the method for preparing wood-steel according to this application, in step 1), the mass concentration of NaOH in the mixed solution is 0.1~10%; preferably 1%. The mass concentration of Na2SO3 in the mixed solution is 1~10%; preferably 3%.

[0009] Using a mixed solution of NaOH and Na2SO3 within the above-mentioned mass concentration range can better promote the decomposition of lignin and hemicellulose in wood, while avoiding excessively high mass concentrations that could lead to corrosion of the cellulose matrix, thereby improving the subsequent densification effect and the mechanical properties of wood-steel composites.

[0010] In a preferred embodiment of the method for preparing wood-steel according to this application, in step 1), the amount of anthraquinone added is 0.1~5g, preferably 1g.

[0011] This application uses anthraquinones within the above-mentioned addition range, which can catalyze the decomposition of lignin and hemicellulose.

[0012] In a preferred embodiment of the method for preparing wood-steel according to this application, in step 1), the ultrasonic cooking time is 6~24h, preferably 8h.

[0013] In some specific embodiments, the temperature in step 1) is 80°C.

[0014] Furthermore, high-temperature ultrasonic cooking can better decompose lignin and hemicellulose in wood, resulting in softened wood (moisture content of over 50%).

[0015] In some specific embodiments, the moisture content of the softened wood is above 50%.

[0016] In some specific embodiments, the natural wood includes Russian / American linden, poplar, etc., with dimensions of 27cm × 20cm or 27cm × 95mm and a thickness of 1cm-5cm. The natural wood can also be common types of wood suitable for wood-steel production.

[0017] In a preferred embodiment of the method for preparing wood-steel as described in this application, in step 2), the ultrasonic cleaning temperature is 80~120℃, the ultrasonic cleaning time is 1~24h, and the number of cleaning cycles is 3~6.

[0018] Preferably, the ultrasonic cleaning temperature is 80°C, the ultrasonic cleaning time is 2-8 hours, and the cleaning is performed 5 times.

[0019] This application uses pure water to ultrasonically clean and soften the wood under the above conditions, repeating the process several times until the water changes from reddish-brown to light red.

[0020] As a preferred embodiment of the method for preparing wood-steel according to this application, in step 2), the organic solvent is an organic solvent that is completely or partially miscible with water and has a boiling point below 100°C.

[0021] In a preferred embodiment of the method for preparing wood-steel according to this application, in step 2), the organic solvent includes at least one of methanol, ethanol, acetone, isopropanol, ethyl acetate, dichloromethane, chloroform, and tetrahydrofuran.

[0022] This application uses the above-mentioned types of organic solvents, which have the following characteristics and effects: 1) Compatibility with water: The selected solvent must be completely or partially miscible with water to ensure that it can enter the cell cavity and cell wall structure of wood through diffusion, thereby effectively replacing free water and some bound water.

[0023] 2) Lower boiling point characteristic: The boiling point is selected to be below 100°C, more preferably below 80°C, so that it can evaporate quickly at a lower temperature during the subsequent hot pressing process, thereby improving drying efficiency and reducing energy consumption.

[0024] 3) Solubility of lignin / hemicellulose: The selected solvent can partially dissolve lignin or hemicellulose, which helps to further reduce the content of non-cellulose components in wood during the replacement process.

[0025] 4) Low surface tension: It facilitates the entry of solvent into the microporous structure through capillary action, thereby improving the displacement efficiency.

[0026] If organic solvents of the above types are not used, such as high-boiling-point solvents or solvents that are immiscible with water, the following problems will occur: they cannot effectively penetrate the internal pore structure of the wood; the water replacement efficiency is significantly reduced; the subsequent drying temperature is increased and the time is prolonged; the drying is uneven, and cracking or warping is likely to occur.

[0027] In a preferred embodiment of the method for preparing wood-steel according to this application, in step 2), the volume ratio of organic solvent to wood is (5~20):1.

[0028] The organic solvent and wood in this application are in the above-mentioned volume ratio, which can provide sufficient mass transfer driving force and concentration gradient. The solvent enters the wood pores through capillary action, replacing free water and part of the bound water, while dissolving part of the lignin / hemicellulose, improving the water replacement efficiency, and subsequently improving the drying effect, thereby improving the quality of the wood-steel composite, while also ensuring the process cost.

[0029] If the volume ratio of organic solvent to wood is less than 5:1, moisture rapidly accumulates in the solvent, reducing the concentration gradient and significantly decreasing the displacement efficiency. This results in high residual moisture levels inside the wood, affecting subsequent drying. If the volume ratio of organic solvent to wood is greater than 20:1, the improvement in displacement efficiency is limited, but it significantly increases solvent consumption and cost, reducing the economic viability of the process.

[0030] In a preferred embodiment of the method for preparing wood-steel according to this application, the immersion time in step 2) is 1~24h.

[0031] In a preferred embodiment of the method for preparing wood-steel as described in this application, in steps 1) and 2), the frequency of ultrasound is 28~120kHz and the duration of ultrasound is 1.5h.

[0032] In some specific embodiments, the frequency of the ultrasound is preferably 40~80 kHz.

[0033] In a preferred embodiment of the method for preparing wood-steel according to this application, the hot-pressing drying conditions in step 3) include: The temperature for hot pressing and drying is 80~120℃, and the drying time is 0.5~6h; The moisture content of the wood-steel planks is less than 1-10%.

[0034] Preferably, the hot-press drying temperature is 90~100℃ and the hot-press drying time is 0.6~2h.

[0035] The preparation method described in this application can significantly shorten drying time, maintain the natural color of wood, reduce cracking and warping, reduce energy consumption, and achieve the dual functions of "dehydration and composition regulation". The process is simple and easy to industrialize.

[0036] Specifically: 1) Because the wood becomes denser during hot pressing, it is difficult for the internal moisture to diffuse out of the fiber channels in traditional drying processes. Therefore, the drying time usually takes tens of hours or even several days. The drying process of this application uses low-boiling-point organic solvents to replace the moisture. During the drying process, the organic solvents can diffuse more easily from the inside of the wood to the surface of the wood, so the drying time can be shortened to about 1 to 2 hours.

[0037] 2) Existing technologies, through multiple water washing, can only remove some lignin and hemicellulose. During hot pressing, the lignin that is not removed from the interior is squeezed out and remains on the wood surface during drying, forming uneven dark stripes or patches. Furthermore, to remove moisture, the wood boards are usually dried at 120°C or higher, which causes carbonization and darkening. This application uses organic solvents to replace moisture, dissolving more lignin and hemicellulose, leaving less residue inside the wood. The drying temperature is below 100°C, resulting in a uniform wood color after drying, preserving its natural wood hue.

[0038] 3) In traditional drying processes, as moisture gradually migrates and evaporates from the surface of the wood towards the interior, a significant moisture gradient easily forms, leading to uneven shrinkage between the inside and outside. This generates substantial drying stress within the wood, resulting in defects such as cracking and warping. This problem is particularly pronounced in dense woods, where the internal structure is even more compact, making moisture migration more difficult. This application employs a solvent replacement method, allowing moisture to be replaced more uniformly by organic solvents, reducing the drastic moisture migration process inherent in traditional drying. Simultaneously, the evaporation process of organic solvents is relatively gentle, helping to alleviate the formation of internal stress. Therefore, this method can significantly reduce the internal stress generated during drying, thereby effectively reducing structural defects such as cracking and warping, and improving the overall structural stability of the material.

[0039] 4) Existing high-temperature drying technologies typically require maintaining high temperatures (100-120°C or even higher) for extended periods, resulting in high equipment energy consumption, low thermal efficiency, and overall high energy consumption, which is detrimental to energy conservation, emission reduction, and green manufacturing. This application utilizes a low-boiling-point organic solvent to replace water, achieving rapid evaporation at lower temperatures (e.g., 80-100°C), significantly reducing the requirements for heating temperature and time. Simultaneously, the significantly shortened drying time leads to a marked reduction in overall energy consumption. Therefore, this method offers significant advantages in energy saving and better aligns with the current needs of green manufacturing and low-carbon development.

[0040] 5) In existing technologies, the drying process is typically only used to remove moisture, with almost no effect on regulating the internal chemical composition of wood. Further removal of lignin and hemicellulose usually requires additional chemical treatment steps, increasing process complexity and cost. This application, in its solvent replacement process, not only achieves moisture substitution but also utilizes the solubility of organic solvents in lignin and hemicellulose, causing partial dissolution during soaking, thereby achieving further regulation of the wood's internal components. This "simultaneous dehydration and component regulation" technical approach not only simplifies the process but also further improves the mechanical properties and stability of the wood.

[0041] 6) While some existing improved drying methods (such as vacuum freeze-drying and supercritical drying) can improve drying effects to some extent, they are usually characterized by complex equipment and high costs, making large-scale industrial applications difficult. The process adopted in this application only adds an organic solvent immersion step and a subsequent low-temperature evaporation step to the traditional hot-pressing process. It requires no complex equipment, is simple in process, and easy to operate. Furthermore, this method can be directly embedded into existing hot-pressing production lines; process upgrades can be achieved by adding a solvent processing unit, demonstrating good industrial compatibility and prospects for large-scale application.

[0042] Compared with the prior art, this application has the following beneficial effects: This application provides a method for preparing wood-based steel suitable for industrial application and with low energy consumption. This method uses a mixed solution and anthraquinone to catalyze the decomposition of lignin and hemicellulose in wood. High-temperature ultrasonic cooking is then used to further decompose the lignin and hemicellulose, yielding softened wood (moisture content above 50%). The softened wood is then immersed in an organic solvent to displace the moisture. The use of a water-miscible solvent ensures that the solvent can diffuse into the wood cell cavities and cell wall structures, effectively replacing free water and some bound water. Simultaneously, the solvent's boiling point is below 100℃. This allows for rapid volatilization at lower temperatures during subsequent hot pressing, improving drying efficiency and reducing energy consumption. Furthermore, the organic solvent with the aforementioned characteristics can partially dissolve lignin or hemicellulose, which helps to further reduce the content of non-cellulose components in the wood during the replacement process. It can also enter the microporous structure through capillary action, improving replacement efficiency. The preparation method provided in this application can achieve rapid drying of hot-pressed wood under low-temperature conditions, avoiding the darkening of wood color during drying, reducing internal stress and structural defects caused by drying, and further optimizing the chemical composition of wood (lignin / hemicellulose) during the drying process. Attached Figure Description

[0043] Figure 1 This is a comparison of the thickness of the linden planks before (left) and after (right) processing. Detailed Implementation

[0044] To better illustrate the purpose, technical solution, and advantages of this application, the following description will be provided in conjunction with the accompanying drawings and specific embodiments.

[0045] In the following examples and comparative examples, unless otherwise specified, the experimental methods used are conventional methods, and the materials and reagents used are commercially available unless otherwise specified. Furthermore, the raw materials used in each parallel experiment are the same.

[0046] Example 1: A method for preparing wood-steel composite. This embodiment provides a method for preparing wood-steel, including the following steps: 1. Lay two linden boards (27cm x 95mm x 1cm) flat in a 30L ultrasonic cleaner (JM100ST-8). Place a stainless steel rack on top, then continue laying linden boards, for a total of four layers. Secure the top layer with a stainless steel plate to prevent subsequent boards from floating.

[0047] 2. Pour 10L of a mixed solution of 1% NaOH (Sines, 98%) and 3% Na2SO3 (Sines, 98%) into an ultrasonic cleaner until the wood board is completely submerged. Then add 1g of anthraquinone (Aladdin, 98%) and continue ultrasonication at 80℃ for 8 hours at a frequency of 40kHz. During this time, the solution level will drop due to the wood board absorbing water, changing from colorless to dark red or even black. The wood board will change from floating on the surface to completely sinking below the surface. Pressing firmly will leave an indentation on the surface of the wood board.

[0048] 3. Drain the liquid from the ultrasonic cleaner, replace it with 10L of water, and continue ultrasonic cleaning at 80℃ for 1.5 hours to remove residual chemical reagents from the wood and dissolve residual lignin and hemicellulose in the water. Repeat the cleaning process 5 times until the solution turns light red and the pH is close to neutral.

[0049] 4. Drain the water from the ultrasonic cleaner and replace it with 15L of 99% industrial alcohol (methanol). Ultrasonicate for 1.5 hours without heating. The water inside the wood board will be replaced by methanol. Repeat the cleaning process once. The residual lignin and hemicellulose in the wood board will be largely removed.

[0050] 5. Remove the wooden boards. Lay two boards flat on a 30 cm × 30 cm × 0.4 cm stainless steel plate, and place another identical stainless steel plate on top. Then place it on a flat vulcanizing machine. Set the temperature of the upper and lower plates of the hot press to 90-100℃, and the pressure of the vulcanizing machine to 2.0 MPa. Start the vulcanizing machine. The solvent in the wood will flow out from both sides along the direction of the wood fibers. After hot pressing for 40-120 minutes, turn off the heating and release the pressure. Remove the wooden boards. The thickness of the boards will be reduced to about one-third of the original thickness, the width perpendicular to the fiber growth direction will increase by about 10%, and the length parallel to the fiber direction will remain basically unchanged. The hot pressing drying temperature is 100℃, and the hot pressing time is 1.5 hours. The final moisture content of the wooden boards is 2.5%.

[0051] A comparison of the thickness of linden planks before (left) and after (right) processing, as shown below. Figure 1 As shown.

[0052] Table 1 shows a comparison of the mechanical strength of linden boards before and after hot pressing.

[0053] Table 1 Example 2: A method for preparing wood-steel composite. Compared with Example 1, the difference is that the solvent in step 4 of Example 2 is different. The solvent is 99% ethanol by volume. The other steps are the same as in Example 1.

[0054] Example 3: A method for preparing wood-steel composite. Compared with Example 1, the difference is that the solvent in step 4 of Example 3 is different. The solvent is acetone with a volume fraction of 99%. The other steps are the same as in Example 1.

[0055] Example 4: A method for preparing wood-steel composite. Compared with Example 1, the difference is that the solvent in step 4 of Example 4 is different. The solvent is isopropanol with a volume fraction of 99%. The other steps are the same as in Example 1.

[0056] Example 5: A method for preparing wood-steel composite. Compared with Example 1, the difference is that the solvent in step 4 of Example 5 is different. The solvent is ethyl acetate with a volume fraction of 99%. The other steps are the same as those in Example 1.

[0057] Example 6: A method for preparing wood-steel composite. Compared with Example 1, the difference is that the solvent in step 4 of Example 6 is different. The solvent is 99% dichloromethane by volume. The other steps are the same as in Example 1.

[0058] Example 7: A method for preparing wood-steel composite. Compared with Example 1, the difference is that the solvent in step 4 of Example 7 is different. The solvent is chloroform with a volume fraction of 99%. The other steps are the same as in Example 1.

[0059] Example 8: A method for preparing wood-steel composite. Compared with Example 1, the difference is that the solvent in step 4 of Example 8 is different. The solvent is tetrahydrofuran with a volume fraction of 99%. The other steps are the same as in Example 1.

[0060] Example 9: A method for preparing wood-steel composite. Compared with Example 1, the difference is that the volume ratio of solvent to wood is different in step 4 of Example 9. 5L of 99% industrial alcohol (methanol) is used instead of 15L of 99% industrial alcohol (methanol). The other steps are the same as in Example 1.

[0061] Example 10: A method for preparing wood-steel composite. Compared with Example 1, the difference is that the volume ratio of solvent to wood is different in step 4 of Example 10, and 20L of 99% industrial alcohol (methanol) is used instead of 15L of 99% industrial alcohol (methanol). The other steps are the same as in Example 1.

[0062] The color and whether the linden boards (wood-steel) prepared in Examples 1-10 were cracked were observed. The results are shown in Table 2.

[0063] Table 2 Comparative Example 1 Compared with Example 1, the difference is that Comparative Example 1 does not perform step 4, does not use organic solvents, and the hot press temperature in step 5 is 120°C for both the upper and lower plates. Other conditions are the same as in Example 1.

[0064] Results: After drying for more than 24 hours, the moisture content at the center of the wood board was 38.4%, and the moisture content at the edge was 15.2%; the surface color of the wood board was reddish-brown.

[0065] Comparative Example 2 Compared with Example 1, the difference is that in Comparative Example 2, dimethyl sulfoxide (DMSO) was used instead of 99% industrial alcohol (methanol), while the other steps were the same as in Example 1.

[0066] After DMSO replacement, the moisture in the wood is partially replaced. However, because DMSO has a high boiling point of 189℃, it is difficult to volatilize during the 100℃ hot-pressing process, leaving a large amount of DMSO and a small amount of moisture inside the wood board. After hot-pressing, the final moisture content of the wood board is approximately 10%–15%, and the residual solvent evaporates slowly, requiring a second vacuum drying process of 6–8 hours to remove it almost completely. The wood board retains a light wood color, but there are slight color differences in some areas. There are no obvious cracks, but there is slight warping.

[0067] Comparative Example 3 Compared with Example 1, the difference is that Comparative Example 3 uses n-hexane instead of 99% industrial alcohol (methanol), while the other steps are the same as in Example 1.

[0068] Because hexane is almost immiscible with water, it has difficulty penetrating the wood and effectively replacing the free and bound water within it, thus retaining a large amount of moisture inside the wood planks. During hot pressing, only a small amount of hexane evaporates from the surface layer, while the residual moisture inside is difficult to expel, resulting in a significant decrease in drying speed. After hot pressing, the moisture content at the center of the wood planks is approximately 25%–35%, and the moisture content at the edges is approximately 8%–12%. Obvious dark brown streaks appear on the surface of the wood planks, and localized cracking and warping occur. The resulting wood-steel structure has poor density and significantly reduced mechanical properties.

[0069] Comparative Example 4 Compared with Example 1, the difference is that the volume ratio of solvent to wood is different in step 4 of Comparative Example 4, and 3L of 99% industrial alcohol (methanol) is used instead of 15L of 99% industrial alcohol (methanol). The other steps are the same as in Example 1.

[0070] The results showed that after drying for approximately 3 hours, the final moisture content in the center of the wood panel was about 18%, while the moisture content at the edges was 1%. Furthermore, some areas of the wood panel retained a dark brown residue. The moisture replacement in the wood panel was incomplete, and some lignin remained.

[0071] Comparative Example 5 Compared with Example 1, the difference is that the volume ratio of solvent to wood is different in step 4 of Comparative Example 5, and 30L of 99% industrial alcohol (methanol) is used instead of 15L of 99% industrial alcohol (methanol). The other steps are the same as in Example 1.

[0072] The results showed that the drying time was approximately 1 hour, the overall moisture content of the wood panels was 1-3%, and there was no dark lignin residue on the surface of the panels, but solvent consumption increased significantly. When the volume ratio of organic solvent to wood is too high, although the improvement in displacement efficiency is limited, it significantly increases the burden of solvent recovery, safety management costs, and volatile organic compound emission pressure, while also raising the requirements for explosion prevention and environmental protection in the production process, which is detrimental to industrial economics.

[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit the scope of protection of this application. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the substance and scope of the technical solutions of this application.

Claims

1. A method for preparing wood-steel composite, characterized in that, Includes the following steps: 1) Soak natural wood in a mixed solution of NaOH and Na2SO3, add anthraquinone as a catalyst, and then ultrasonically cook it at a temperature of 80~120℃ to obtain softened wood; 2) Ultrasonic cleaning of the softened wood from step 1), then immersing the cleaned wood in an organic solvent, ultrasonically displacing the moisture from the wood to obtain the treated wood. 3) The wood treated in step 2) is hot-pressed and dried to obtain wood-steel; The organic solvent has a boiling point below 100℃ and is miscible with water.

2. The method for preparing wood-steel as described in claim 1, characterized in that, In step 1), the mass concentration of NaOH in the mixed solution is 0.1% to 10%. The mass concentration of Na2SO3 in the mixed solution is 1~10%.

3. The method for preparing wood-steel as described in claim 1, characterized in that, In step 1), the amount of anthraquinone added is 0.1~5g.

4. The method for preparing wood-steel as described in claim 1, characterized in that, In step 1), the ultrasonic cooking time is 6~24h.

5. The method for preparing wood-steel as described in claim 1, characterized in that, In step 2), the ultrasonic cleaning temperature is 80~120℃, the ultrasonic cleaning time is 1~24h, and the number of cleaning cycles is 3~6.

6. The method for preparing wood-steel as described in claim 1, characterized in that, In step 2), the organic solvent is an organic solvent that is completely or partially miscible with water and has a boiling point below 100°C.

7. The method for preparing wood-steel as described in claim 6, characterized in that, In step 2), the organic solvent includes at least one of methanol, ethanol, acetone, isopropanol, ethyl acetate, dichloromethane, chloroform, and tetrahydrofuran.

8. The method for preparing wood-steel as described in claim 1, characterized in that, In step 2), the volume ratio of organic solvent to wood is (5~20):

1.

9. The method for preparing wood-steel as described in claim 1, characterized in that, In step 2), the frequency of the ultrasound is 28~120kHz, and the duration of the ultrasound is 1.5h.

10. The method for preparing wood-steel as described in claim 1, characterized in that, In step 3), the conditions for hot-press drying include: The temperature for hot pressing and drying is 80~120℃, and the drying time is 0.5~6h; The moisture content of the wood-steel planks is less than 1-10%.